Amorphous znS-3 and application and preparation method thereof

CN122875255APending Publication Date: 2026-10-09HUAIBEI NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611362057.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-03
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

然而由于光催化反应动力学缓慢,CO2分子的惰性和反应过程的复杂性,导致其光生载流子的分离与利用效率和催化效能低

Benefits of technology

[0014]本发明通过构建非晶态ZnS催化剂,系统研究了非晶化工程对光热催化CO2还原制备高附加值C2燃料性能的影响及其作用机制,重点探究了ZnS非晶化过程中晶体结构演变、Zn-S键长变化及晶格畸变对催化性能的影响。结果表明,非晶ZnS-3催化剂表现出优异的光热催化CO2还原性能,其乙烯生成速率最高达到744.7 μmol·g-1·h-1。实验表征结合密度泛函理论(DFT)计算表明,引入硫空位(VS)能够有效促进光生电子转移,调控局域电子结构并减小晶格常数,同时优化关键中间体*CO的吸附行为,促进C-C偶联过程,从而提高C2产物的生成效率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122875255A_ABST
    Figure CN122875255A_ABST
Patent Text Reader

Abstract

The application discloses application of amorphous ZnS-3 which is used as a catalyst for efficiently photo-thermal synergistic reduction of CO2 to ethylene; in the amorphous ZnS-3, the molar ratio of zinc and sulfur is 1:3. The application also discloses a preparation method of the amorphous ZnS-3, which comprises the following steps: weighing zinc nitrate hexahydrate and thiourea solid in a reaction container; adding a glycol-free solution and stirring, denoted as solution A; transferring the solution A into an autoclave container, and reacting; centrifugally collecting white powder, washing the white powder with ultrapure water and ethanol alternately for 2-4 times, and drying the precipitate in a vacuum environment to obtain the amorphous ZnS-3. The amorphous ZnS-3 has excellent photo-thermal catalytic CO2 reduction performance, the highest ethylene generation rate reaches 744.7 μmol·g ‑1 ·h ‑1 , and the ethylene selectivity reaches 94.08%, the catalytic performance is significantly better than that of a pure photocatalytic system and a pure thermal catalytic system, and it is proved that there is an obvious synergistic promotion effect between light energy and heat energy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of photothermal catalysis technology, and in particular to an amorphous ZnS-3 and its applications and preparation methods. Background Technology

[0002] Utilizing solar energy to convert CO2 into high-value-added C2 fuels has been recognized as an effective way to alleviate the energy crisis and the greenhouse effect, and is of great significance to the future realization of the "carbon cycle" strategy. Metal sulfides, with their suitable band gaps and wide photoresponse range, have become strong contenders in this field. Furthermore, with the rapid development of metal sulfides, their physical properties are constantly being altered through various engineering strategies, including elemental doping, heterostructure construction, interface building, and phase transformation. Amorphous sulfides, due to their disordered and chaotic structure, expose more catalytically active sites. Therefore, applying amorphization engineering as a structural control strategy to photothermal catalysis systems provides new design ideas for the efficient and selective conversion of CO2 into high-value-added C2 products.

[0003] Photocatalytic CO2 reduction has become a widely studied emission reduction scheme due to its advantages of operation under ambient temperature and pressure and environmental friendliness. However, the slow photocatalytic reaction kinetics, the inertness of CO2 molecules, and the complexity of the reaction process result in low efficiency in the separation and utilization of photogenerated carriers and low catalytic performance. Wang et al. designed a zinc-gallium binary catalyst to improve the photocatalytic activity to 490.3 μmol·h⁻¹. -1 The CO yield was improved, and the selectivity of CO was targetedly enhanced. On the other hand, by fully utilizing the photothermal effect to accelerate surface reaction kinetics, novel photothermal catalysis not only retains the high selectivity of photocatalysis but also exhibits the conversion rate of thermocatalysis at low temperature and low pressure. For example, Chen's research group proposed a photothermal synergistic effect for C2 product generation. By regulating the Mo-Cu dual-site stabilization of the *CHO intermediate, the selectivity of C2 products was improved. Single-atom Cu doping on MoS2 was used to enhance light absorption, thereby enhancing CO2 adsorption and *CHO accumulation at S sites. Photothermal synergy can effectively overcome the limitations of traditional photocatalysis and thermocatalysis, providing a new technical route for the efficient and selective conversion of CO2 into high-value-added C2 products such as ethanol.

[0004] In recent years, converting CO2 into valuable chemicals has become a research hotspot. For example, Lin et al. constructed a ZnIn2S4-AlOOH composite photocatalyst, achieving a CO2 adsorption and activation efficiency of 510.3 μmol·g by constructing hindered Lewis acid-base pairs to promote CO2 adsorption and activation. -1 ·h -1The CO generation rate was significantly improved, enhancing the photocatalytic reduction performance of CO2. Furthermore, Zhang et al. proposed an in-situ atmosphere control strategy, achieving nearly 100% selectivity for the photocatalytic reduction of CO2 to CH4 by regulating the adsorption and hydrogenation process of *CO intermediates on the catalytic surface, providing a new design approach for highly selective methane generation. Further, Jaksani et al. constructed a MOF-derived CuO / TiO2 heterojunction and combined it with an AI-assisted continuous flow reactor to achieve highly efficient photocatalytic CO2 reduction to methanol, providing a new strategy for solar-driven liquid fuel synthesis. Therefore, developing a photocatalytic system that uses CO2 and H2O as raw materials to achieve efficient and highly selective preparation of high-value-added solar fuels under mild conditions is of great significance for realizing the resource utilization of CO2 and carbon cycling.

[0005] ZnS, as a typical group II-VI compound semiconductor, has a relatively negative conduction band position (approximately 1.85 V). vs ZnS, with its relatively wide band gap and high redox potential, possesses strong photogenerated electron reduction capabilities and has attracted widespread attention in the field of CO2 photocatalytic reduction. Under illumination, ZnS can generate photogenerated electron-hole pairs with strong redox capabilities, thus it is considered a photocatalytic material with broad application prospects. For example, Zhu et al. reported the preparation of ZnS nanomaterials with different particle sizes by controlling the addition amounts of polyvinyl glycol, hexadecyltrimethylammonium bromide, and sodium dodecyl sulfate. They achieved a hydrogen production of 11.47 mmol·g⁻¹ after 5 h of illumination. -1 Exhibiting excellent photocatalytic performance, Wang et al. successfully constructed an amorphous sulfide photocatalyst by controlling the amorphization degree of ZnCdS. Their research found that the amorphous structure can induce local dipole recombination, optimize the electronic structure, and promote the separation of photogenerated carriers, thereby significantly improving photocatalytic performance. This provides a new approach for the amorphization engineering design of highly efficient photocatalysts. Amorphization engineering is considered an important strategy for improving photocatalytic performance because it can reconstruct the local electronic structure of the catalyst, introduce abundant defect sites, and expose more uncoordinated active sites. During the preparation of ZnS catalysts, it was found that changes in the sulfur source content affected the vacancy content and influenced the catalyst's crystal form to amorphous form. Simultaneously, it lowered the CO2 adsorption energy, increasing the CO2 adsorption capacity through the increase of surface active sites. Summary of the Invention

[0006] The purpose of this invention is to provide an amorphous ZnS-3 catalyst, its applications, and its preparation method. By constructing an amorphous ZnS catalyst, the influence and mechanism of amorphization engineering on the photothermal catalytic reduction of CO2 to produce high-value-added C2 fuel were systematically studied. The effects of crystal structure evolution, Zn-S bond length changes, and lattice distortion during ZnS amorphization on catalytic performance were investigated in detail. Based on these findings, it was discovered that the amorphous ZnS-3 catalyst exhibits excellent photothermal catalytic CO2 reduction performance.

[0007] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides an application of amorphous ZnS-3, wherein the amorphous ZnS-3 serves as a catalyst for the efficient photothermal synergistic reduction of CO2 to ethylene; In the amorphous ZnS-3, the molar ratio of zinc to sulfur is 1:3.

[0008] In some possible implementations, the method for reducing CO2 to produce ethylene includes the following steps: Weigh amorphous ZnS-3 and deionized water at a solid-liquid mass ratio of 1:200, add them to the reaction vessel and seal it. Rinse the reaction vessel with carbon dioxide gas through the air inlet for 14-16 minutes to remove residual air. Close the exhaust valve, stabilize the carbon dioxide pressure at 0.09-0.11 MPa, stir magnetically for 25-35 min in the dark, then turn on the 250-350 W xenon lamp and set it to 245-255 ℃. Start timing and let the reaction last for 1-3 h. After the reaction was completed, the gas inside the reactor was quantitatively determined using a Shimadzu GC-2014C gas chromatograph.

[0009] The present invention also provides a method for preparing the amorphous ZnS-3 described in the first aspect, comprising the following steps: Weigh zinc nitrate hexahydrate solid and thiourea solid into a reaction vessel; Add ethylene glycol, stir, and label this solution A. The solution A is transferred to an autoclave for reaction; The white powder was collected by centrifugation, and then washed 2-4 times alternately with ultrapure water and ethanol. The precipitate was dried in a vacuum environment to obtain amorphous ZnS-3.

[0010] In some possible implementations, the content of the deethylene glycol is 60-80 mL, and the concentration is ≥99.5%.

[0011] In some possible implementations, the stirring rate is set to 400-600 rpm and the stirring time to 40-50 min.

[0012] In some possible implementations, the reaction temperature is set to 160-200 °C and the reaction time is set to 8-12 h.

[0013] In some possible implementations, the drying temperature is set to 50-70 °C.

[0014] This invention constructs an amorphous ZnS catalyst and systematically studies the effects and mechanisms of amorphization engineering on the photothermal catalytic reduction of CO2 to produce high-value-added C2 fuels. The focus is on investigating the influence of crystal structure evolution, Zn-S bond length changes, and lattice distortion during ZnS amorphization on catalytic performance. The results show that the amorphous ZnS-3 catalyst exhibits excellent photothermal catalytic CO2 reduction performance, with the highest ethylene production rate reaching 744.7 μmol·g⁻¹. -1 ·h -1 Experimental characterization combined with density functional theory (DFT) calculations show that the introduction of sulfur vacancies (V... S It can effectively promote photogenerated electron transfer, regulate the local electronic structure and reduce the lattice constant, while optimizing the adsorption behavior of the key intermediate *CO, promoting the CC coupling process, thereby improving the generation efficiency of C2 products.

[0015] This invention, by simulating the evolution of ZnS from a crystalline to an amorphous state, further reveals the different V... S The influence of sulfur content on catalytic performance was investigated, and the promoting effect of appropriate sulfur vacancy concentration on photothermal catalytic CO2 reduction was clarified.

[0016] This invention systematically compares the photothermal catalytic performance and reaction mechanism of crystalline ZnS and amorphous ZnS with different sulfur vacancy contents, providing new research ideas for the design of amorphous semiconductor photothermal catalysts and the high-value utilization of CO2. Attached Figure Description

[0017] Figure 1 The following are provided for this invention: (a) the preparation process of the catalyst; (b) the XRD pattern of the catalyst; (c) the EPR spectrum of the catalyst; (d) the radial distribution function of the ZnS-3 catalyst; (ef) the molecular dynamics simulation structure comparison diagram of ZnS-3; (g) the structure diagram of the ZnS-3 catalyst; and (h) the structure diagram of the ZnS-5 catalyst. Figure 2Morphological and microstructural analysis of ZnS-3 provided for this invention; (ad) SEM and TEM images of ZnS-3; (e) Zn K-edge XANES spectra of Zn-foil, ZnO-simple, ZnS-1 and ZnS-3; (f) Fourier transform EXAFS of Zn K-edge of Zn-foil, ZnO-simple, ZnS-1 and ZnS-3; (g) K-spectrum of Zn-foil, ZnO-simple, ZnS-1 and ZnS-3; (hj) Full-range EXAFS WT plot of ZnO-simple, ZnS-1 and ZnS-3; Figure 3 TMPO-e of (ab)ZnS-1 and ZnS-3 provided by this invention - Spectra; TEMPO-h of (cd) ZnS-1 and ZnS-3 + Spectroscopy; (e) Electrochemical impedance spectroscopy; (f) Photocurrent response spectroscopy; (g) Fluorescence spectrum; (h) Transient fluorescence spectrum; (i) LSV spectrum of the catalyst; Figure 4 This invention provides (a) the catalytic activity of catalyst ZnS-3 and ZnS doped with different sulfur source contents under light irradiation and 250 °C conditions; (b) the catalytic activity of catalyst ZnS-3 under light irradiation, 250 °C and light irradiation at 250 °C conditions; (c) the effect of catalyst ZnS-3 on catalytic activity under different CO2 pressures; (d) the effect of catalyst ZnS-3 on catalytic activity under different reaction temperatures; (e) the effect of ZnS-3 with different light intensities on catalytic activity; (f) cyclic experiments; (g) carbon dioxide adsorption model of sample ZnS-1; (h) carbon dioxide adsorption model of sample ZnS-3; and (i) carbon dioxide adsorption model of sample ZnS-5. Figure 5 This is a schematic diagram of the reaction mechanism for the photothermal selective reduction of CO2 to C2H4 on amorphous ZnS-3 provided by the present invention; Figure 6 The Raman spectra of Example 1 and Comparative Examples 1-4 are shown below. Figure 7 This is a schematic diagram of the catalyst structure of ZnS-1; Figure 8 X-ray photoelectron spectra of ZnS-1 and ZnS-3; Figure 9 SEM and TEM images of ZnS-1; Figure 10 SEM image of ZnS-3; Figure 11 SAED plot of ZnS-3; Figure 12TEM-EDS plot of ZnS-3; Figure 13 Hydrothermal processing images of Zn-foil and ZnO-simple; Figure 14 Thermogravimetric analysis (TGA) curves for ZnS-3; Figure 15 CO2-TPD curves for ZnS-1, ZnS-3, and ZnS-5; Figure 16 BET images for different ZnS (ZnS-1, ZnS-3, ZnS-5); Figure 17 The following are the results of the reduction yield of ZnS-3 to carbon dioxide under different conditions: (a) Thermal imaging results of ZnS-3 after stabilization under photothermal conditions for 5 min; (b) Optimal carbon dioxide pressure was studied under fixed conditions (250 ℃, 50 mg catalyst, 2 h reaction time); (c) Optimal temperature screening was carried out under fixed conditions (50 mg catalyst, 0.1 MPa, 2 h reaction time); (d) Photothermal catalytic activity curves of ZnS-3 for ethylene production at different wavelengths; (e) Cyclic experiment.

[0018] Figure 18 UV-Vis diffuse reflectance spectra of different ZnS (ZnS-1, ZnS-3, ZnS-5); Figure 19 Mott-Schottky curves (a) ZnS-1; (b) ZnS-3; Figure 20 XPS images of ZnS-3 in (a) used and unused states; (b) XPS images of Zn in ZnS-3 ... Figure 21 In-situ FTIR spectroscopic analysis of ZnS-5. Detailed Implementation

[0019] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of the embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application. At the same time, in the description of the embodiments of this application, the terms "first," "second," etc., are only used to distinguish descriptions and should not be construed as indicating or implying relative importance. Thus, features defined with "first" and "second" may explicitly or implicitly include one or more features. In the description of the embodiments of this application, "multiple" means two or more, unless otherwise explicitly specified.

[0020] Example 1 This embodiment provides an amorphous ZnS-3 as a catalyst for the efficient photothermal synergistic reduction of CO2 to ethylene; in the amorphous ZnS-3, the molar ratio of zinc to sulfur is 1:3.

[0021] The preparation method of amorphous ZnS-3 includes the following steps: Weigh 1 mmol of zinc nitrate hexahydrate solid Zn(NO3)2·6H2O and 3 mmol of thiourea solid CH4N2S into a reaction vessel; Add deethylene glycol, stir, set the stirring speed to 500 rpm, and stir for 45 min. This is recorded as solution A. The deethylene glycol content is 70 mL, and the concentration is ≥99.5%.

[0022] Transfer solution A to an autoclave and allow it to react. Set the reaction temperature to 180 °C and the reaction time to 10 h. The white powder was collected by centrifugation, and then washed three times with ultrapure water and ethanol alternately. The precipitate was dried overnight in a vacuum environment at a temperature of 60 °C to obtain amorphous ZnS-3.

[0023] The method for producing ethylene from CO2 by reducing amorphous ZnS-3 includes the following steps: Weigh 50 mg of amorphous ZnS-3 and 10 mL of deionized water, add them to the reaction vessel and seal it. Rinse the reaction vessel with carbon dioxide gas through the air inlet for 15 min to remove residual air. Close the exhaust valve, stabilize the carbon dioxide pressure at 0.1 MPa, stir magnetically for 30 min in the dark, then turn on the 300 W xenon lamp for irradiation, set the temperature to a constant 250 °C, start timing, and let the reaction last for 2 h. After the reaction was completed, the gas inside the reactor was quantitatively determined using a Shimadzu GC-2014C gas chromatograph.

[0024] Comparative Example 1 The only difference between this comparative example and Example 1 is that the catalyst is amorphous ZnS-1, wherein the molar ratio of zinc to sulfur is 1:1, and 1 mmol of zinc nitrate hexahydrate solid Zn(NO3)2·6H2O and 1 mmol of thiourea solid CH4N2S are weighed.

[0025] Comparative Example 2 The only difference between this comparative example and Example 1 is that the catalyst is amorphous ZnS-2, wherein the molar ratio of zinc to sulfur is 1:2, and 1 mmol of zinc nitrate hexahydrate solid Zn(NO3)2·6H2O and 2 mmol of thiourea solid CH4N2S are weighed.

[0026] Comparative Example 3 The only difference between this comparative example and Example 1 is that the catalyst is amorphous ZnS-5, in which the molar ratio of zinc to sulfur is 1:5, and 1 mmol of zinc nitrate hexahydrate solid Zn(NO3)2·6H2O and 5 mmol of thiourea solid CH4N2S are weighed.

[0027] Comparative Example 4 The only difference between this comparative example and Example 1 is that the catalyst is amorphous ZnS-6, in which the molar ratio of zinc to sulfur is 1:6, and 1 mmol of zinc nitrate hexahydrate solid Zn(NO3)2·6H2O and 6 mmol of thiourea solid CH4N2S are weighed.

[0028] Figure 1 (b) shows the XRD patterns of samples from Example 1 and Comparative Examples 1-4, where ZnS-1 and ZnS-3 exhibit obvious XRD characteristic peaks. The XRD peaks of the ZnS samples are located at 26.89 °, 28.51 °, 30.53 °, 47.58 °, 51.87 °, and 56.39 °, corresponding to the (100), (002), (101), (110), (103), and (112) crystal planes of hexagonal wurtzite ZnS, respectively. This confirms that the compound prepared by the solvothermal method is pure-phase ZnS. With the change of thiourea content, no new impurity phase diffraction peaks appeared in any of the samples, indicating that the sulfur source regulation did not change the crystal phase structure of ZnS. At the same time, the positions of each characteristic peak remained basically unchanged, indicating that the introduction of sulfur vacancies did not cause significant overall distortion of the ZnS lattice, but mainly changed the local coordination environment.

[0029] Figure 6 The Raman spectra of Sample 1 (Example 1) and Comparative Examples 1-4 further validate the ZnS structure in the samples. The ZnS spectrum is at 250.74 cm⁻¹. -1 334.16 cm -1The peaks at [value] are attributed to the transverse optical (TO) and longitudinal optical (LO) phonon modes, respectively. With the increase of sulfur vacancies, the characteristic peaks exhibit a certain blue shift, indicating that the addition of vacancies introduces lattice defects into ZnS. The main peak is at 250.74 cm⁻¹. -1 The blue shift indicates an increase in the Zn-S bond force constant, which is consistent with the synchrotron radiation results, and the two corroborate each other.

[0030] Figure 1 (c) EPR spectra of samples from Example 1 and Comparative Examples 1-4, where the signal intensity of ZnS-1 is negligible. Within a certain range, the EPR signal increases with the increase of sulfur source, indicating that the vacancy concentration of ZnS also increases with the increase of sulfur source, and the g value is 2.003, originating from the signal site of sulfur vacancy. The signal order is as follows: ZnS-5 > ZnS-6 > ZnS-3 > ZnS-2 > ZnS-1. To further reveal the formation mechanism of the ZnS-3 amorphous structure, AIMD simulation was performed. The melt-quench method was used, and the amorphous model was constructed by fully melting at 3000 K and then rapidly cooling to room temperature. The RDF shows that the first nearest neighbor Zn-S still maintains a significant peak, while the periodicity gradually disappears in the medium and long range, indicating that ZnS-3 maintains the amorphous structure characteristics of short-range order and long-range disorder. At the same time, the first peak of PDF is significantly broadened, and the valley value between the first and second peaks is significantly raised, further proving that the amorphous structure has been formed. The decrease in the height of the main peak, along with the appearance of a non-zero "valley" between the first and second peaks, indicates sufficient structural relaxation.

[0031] Figure 1 (e) and (f) show the amorphous structures constructed by AIMD of amorphous ZnS-3 after high temperature and cooling, exhibiting short-range order and long-range disorder characteristics.

[0032] Figure 7 and Figure 1 (g) and (h) represent the structural configurations of ZnS-1, ZnS-3, and ZnS-5, respectively. X-ray photoelectron spectroscopy (XPS) was used to analyze the chemical composition and elemental valence states of ZnS-1 and ZnS-3. Figure 8 As shown in (a), the main active elements Zn and S in amorphous ZnS-3 are consistent with the EDS analysis results, and the full spectrum and detection scans of ZnS-1 and ZnS-3 are almost identical.

[0033] X-ray photoelectron spectroscopy (XPS) analysis was performed on ZnS-1 and ZnS-3, such as... Figure 8 As shown in (b), both ZnS-1 and ZnS-3 are in Zn 2p The region exhibits two characteristic peaks, corresponding to Zn. 2p 3 / 2 and Zn 2p 1 / 2This indicates that Zn is mainly composed of Zn 2+ It exists in form. Compared to ZnS-1, Zn in ZnS-3... 2p The characteristic peaks shifted towards lower binding energies, indicating an increase in the local electron density around Zn atoms and a redistribution of the electron cloud after the introduction of sulfur vacancies. This suggests that the formation of sulfur vacancies during amorphization alters the local coordination environment of Zn atoms, further confirming the presence of a high concentration of sulfur vacancy defects in ZnS-3. Sulfur vacancy-induced electronic structure modulation is beneficial for improving the electron-supplying capacity of the catalyst, providing more electrons for the adsorption and activation of CO2 molecules, thereby promoting the photothermal catalytic CO2 reduction reaction.

[0034] like Figure 8 As shown in (c), the S of ZnS-1 and ZnS-3 2p The spectra can all be decomposed into two characteristic peaks located at approximately 161.45–161.70 eV and 162.56–162.93 eV, respectively, which are attributed to S. 2- S 2p 3 / 2 and S 2p 1 / 2 Compared to ZnS-1, ZnS-3 contains more S... 2p The characteristic peaks shifted by approximately 0.25 eV towards lower binding energies, further indicating that the introduction of sulfur vacancies led to a reconstruction of the local electronic structure, causing a change in the electron density around the S atom. Simultaneously, the S in ZnS₃… 2p The significantly reduced peak area indicates a decrease in sulfur content in the sample, consistent with the increase in sulfur vacancy concentration. Abundant V S It can provide more CO2 adsorption and activation sites and promote interfacial electron transfer, thereby improving the photothermal catalytic CO2 reduction performance.

[0035] The morphology and microstructure of the prepared photothermal catalysts were observed using scanning electron microscopy (SEM) and transmission electron microscopy (TEM). SEM and TEM images of ZnS-1 and ZnS-3 are shown below. Figure 9 (a)(b) Figure 2 (a) and Figure 10 As shown, both ZnS-1 and ZnS-3 exhibit aggregated granular structures. S The morphology of ZnS-3 did not change significantly after the addition, but the lattice fringes changed. High-resolution TEM images of ZnS-1 and ZnS-3 showed lattice spacings of 0.308 nm and 0.2991 nm, respectively, corresponding to the (002) crystal plane of hexagonal wurtzite ZnS (JCPDS No. 36-1450). Figure 11The electron diffraction patterns also confirm this, showing that the (002) and (100) crystal planes indicate the successful preparation of amorphous ZnS-3, and correspond to the main characteristic peaks detected in XRD. Compared with ZnS-1, the continuity of lattice fringes on the same crystal plane in ZnS-3 is interrupted, which leads to lattice shrinkage and a decrease in lattice spacing. S The introduction of sulfur disrupts the periodic arrangement of the ZnS lattice, resulting in local disordered regions and lattice distortion. This indicates that sulfur vacancies induce local reconstruction of the ZnS lattice, giving the material a higher degree of structural disorder. Figure 12 The EDS elemental mapping diagram of the catalyst ZnS-3 shows that Zn and S elements are uniformly distributed on ZnS-3, which further confirms the successful preparation of the ZnS-3 catalyst.

[0036] To confirm V S The changes in zinc valence state with increasing concentration and the elucidation of the local coordination environment were investigated. X-ray absorption near-edge structure (XANES) and extended X-ray absorption fine structure analysis were performed on Zn-foil, ZnO-simple, ZnS-1, and ZnS-3 at the K-edge of Zn. The position of the absorption edge is extremely sensitive to the valence state of the absorbing atoms. The absorption edges of ZnS-1 and ZnS-3 are located between Zn-foil (reference sample with valence state 0) and ZnO-simple (reference sample with valence state +2), as shown in the figure. Figure 2 As shown in (e), their average valence ranges from 0 to +2. Compared to ZnS-1, ZnS-3 has more V... S These V S Acting as an electron donor, it introduces excess electrons into the local electronic structure, increasing the local electron density of adjacent zinc atoms, indicating a decrease in the average valence state of Zn. Therefore, this XANES analysis directly confirms the electrical compensation mechanism proposed earlier from EPR and XPS data, forming a content map of the electronic effects of defect engineering.

[0037] To gain a more detailed understanding of the local atomic arrangement and bond lengths around zinc atoms, Figure 2 (f) The K-space spectra of the Fourier transform in R-space were analyzed. The prominent peaks in the R-space spectra correspond to specific atomic coordination shells surrounding the central absorbing atom (zinc). For zinc sulfide, the main peak at approximately 1.91 is characteristic of the first coordination shell, specifically representing the Zn-S coordination bond. Figure 2As shown in (f), compared with ZnS-1, the intensity of the first coordination peak in ZnS-3 is significantly reduced, indicating a decrease in the Zn-S coordination number around the Zn atom and an increase in local structural disorder, which is consistent with the introduction of sulfur vacancies. After the formation of sulfur vacancies, the local coordination environment changes, and local structural relaxation occurs in neighboring Zn atoms, leading to a rearrangement of Zn-S bonds and a slight shortening of the average Zn-S bond length, from 2.32 ± 0.02 Å to 2.30 ± 0.02 Å (specific parameters are shown in Table S1). Simultaneously, sulfur vacancies reduce the coordination number of Zn atoms and increase local structural disorder, thus significantly weakening the intensity of the first coordination peak. This confirms the valence state analysis of XANES and provides a comprehensive chain of evidence for successful defect engineering.

[0038] To further quantify these coordination environments, an EXAFS fitting analysis was performed, and the fitting results are as follows: Figure 2 As shown in (g), the specific parameters are listed in Table 1. The average coordination number for pure zinc (Zn-foil) is 6, while the average coordination number for ZnO is approximately 4, which is consistent with the theoretical coordination environment of ZnO crystals. In ZnS-1 and ZnS-3 samples, the Zn-S coordination numbers are approximately 2.17 and 1.32, respectively. Combined with the EPR results, this further confirms the successful construction of sulfur vacancies in ZnS. Further support for EXAFS analysis was provided by wavelet transform (WT) analysis, as shown... Figure 2 (hj) and Figure 13 As shown, compared with ZnS-1, the position of the Zn-S scattering signal in the WT contour plot of ZnS-3 sample is slightly shifted, and the scattering intensity is reduced. This further indicates that the introduction of sulfur vacancies changes the local coordination environment of Zn atoms and leads to the adjustment of Zn-S bond length and coordination structure.

[0039] Table 1 Figure 14 The thermogravimetric curve (TGA) of ZnS-3 is shown, i.e., the TGA curve of the ZnS-3 sample under nitrogen conditions. The weight loss below 100 °C is mainly due to the evaporation of adsorbed moisture on the material surface, while the weight loss at 300-400 °C may be due to some thiourea residue. Experimental results show that the ZnS-3 sample exhibits good stability at the experimental temperature of 250 °C, retaining 95.1% of its weight. Therefore, the catalyst exhibits strong stability under the experimental conditions of 250 °C. Figure 15As shown, compared with ZnS-1, the CO2 desorption peak temperature of ZnS-3 decreased from 340.12 ℃ to 309.83 ℃, indicating a weakening of the binding strength between CO2 and the catalyst surface. Meanwhile, ZnS-3 exhibited a larger desorption peak area, indicating that it has more available CO2 adsorption sites. A moderate adsorption strength is beneficial for both the adsorption and activation of CO2 molecules and avoids excessive adsorption of reaction intermediates, thus facilitating subsequent catalytic reactions. Furthermore, the nitrogen physical adsorption analysis (BET) spectrum is shown below. Figure 16 As shown, the ZnS-1 catalyst exhibits a type II adsorption isotherm and an H3-type hysteresis loop, indicating that the material mainly consists of a slit-like mesoporous structure formed by particle packing. As shown in Table 2, the BET specific surface area of ​​ZnS-3 is 130.948 m². 2 / g, with a pore size range of 10.2742 nm, while the BET specific surface area of ​​ZnS-1 is 62.1236 m² / g. 2 / g, with a pore size range of 24.0647 nm, it can be clearly seen that the addition of vacancies exposes more surface defect sites and increases the contact probability and adsorption amount of carbon dioxide in the sample, which is beneficial to improving the adsorption and activation efficiency of CO2 molecules, thereby promoting the subsequent multi-electron reduction reaction.

[0040] Table 2 To investigate the e during the redox process - and h + The effect of the reduction reaction was investigated using 2,2,6,6-tetramethylpiperidine-1-oxygen radical (TEMPO) as the e- radical. - h + The trapping agent underwent ESR testing, and the results were as follows: Figure 3 As shown in (ad), both crystalline ZnS-1 and amorphous ZnS-3 catalysts exhibit the classic TEMPO-e bonding properties when combined with TEMPO. - TEMPO-h + The adduct exhibits a 1:1:1 uniform triplet signal, in which TEMPO-e - The signal intensity decreased after 5 minutes of illumination in both cases. The signal intensity of crystalline ZnS-1 decreased by 52.90% after 5 minutes of illumination, while the signal intensity of amorphous ZnS-3 decreased even faster, by 58.43% within the same timeframe. This indicates that under the same illumination, amorphous ZnS-3 generated and transmitted more photogenerated electrons compared to crystalline ZnS-1. - TEMPO-h +The signal intensity also showed the same trend. After 5 minutes of illumination, the signal intensity of crystalline ZnS-1 decreased by 17.51%, while the signal intensity of amorphous ZnS-3 decreased even faster, by 21.77% in the same time period. This indicates that amorphous ZnS-3 has a higher h + Production efficiency. The above results indicate that introducing an appropriate amount of V... S After forming an amorphous structure, it can effectively promote the generation and migration of photogenerated carriers, providing more active electrons for the CO2 reduction reaction.

[0041] To further analyze charge transport behavior, electrochemical impedance spectroscopy (EIS) was performed using samples from Examples 1 and Comparative Examples 1-4 (5 mm × 5 mm, FTO / CAT.) as working electrodes, an Ag / AgCl electrode (in 3 M KCl solution) as reference electrodes, and a Pt wire as the counter electrode in a standard three-electrode cell. Thin-film working electrodes were prepared by drop-casting the sample with H₂O suspension onto an FTO glass substrate and then air-drying overnight. An aqueous solution containing K₃[Fe(CN)₆] (0.01 M) and K₄[Fe(CN)₆] (0.01 M) and 0.05 M KCl was used as the electrolyte.

[0042] like Figure 3 As shown in (e), ZnS-3 has the smallest Nyquist semicircle radius, indicating that it has the lowest interfacial charge transfer resistance. Photogenerated carriers can migrate to the catalyst surface more quickly to participate in the reaction, which is beneficial to improving CO2 reduction kinetics. Figure 3 The transient photocurrent test in (f) further confirmed the above conclusions. Amorphous ZnS-3 exhibited the highest photocurrent response, with the order of magnitude as follows: ZnS-3 > ZnS-5 > ZnS-6 > ZnS-2 > ZnS-1. This trend is consistent with the observed carbon dioxide reduction performance, proving that crystalline ZnS-1 is appropriately doped with V. S This can subsequently improve charge separation and transfer efficiency. Steady-state photoluminescence (PL) testing was used to study the recombination of photogenerated carriers; the intensity of photoluminescence is proportional to the recombination rate of electron-hole pairs. For example... Figure 3 As shown in (g), the PL emission intensity of amorphous ZnS-3 is weaker than that of crystalline ZnS-1, indicating that the crystalline ZnS-1 exhibits lower PL emission intensity with increasing V. S Both methods enhanced the transfer and separation of photogenerated carriers, but compared to others, within a certain range, with V... S The emission intensity of PL decreases with increasing concentration, reaching its optimal value in amorphous ZnS⁻³. To further investigate carrier dynamics, time-resolved PL (TRPL) measurements were performed. Figure 3(h) indicates that the average PL lifetime of the amorphous ZnS-3 sample (τ = 2.69 ns) is shorter than that of the crystalline ZnS-1 sample (τ = 2.87 ns), further confirming the satisfactory charge separation in the samples. Furthermore, linear sweep voltammetry (LSV) testing further evaluated the electrocatalytic performance of the catalyst. Figure 3 As shown in (i), ZnS-3 has the lowest initial overpotential, which is significantly lower than that of ZnS-1 and V. S Excessive ZnS-5 indicates an inadequate amount of vitamin V. S This can effectively lower the energy barrier of the CO2 reduction reaction, accelerate the interfacial electron transfer process, and thus improve the kinetics of the CO2 photothermal reduction reaction. In summary, an appropriate amount of V... S The induced amorphous ZnS-3 not only improves the generation, separation and migration efficiency of photogenerated carriers, but also reduces the interfacial charge transfer resistance and CO2 reduction overpotential, ultimately achieving superior photothermal catalytic CO2 reduction performance.

[0043] Catalyst activity was tested on samples from Example 1 and Comparative Examples 1-4. 50 mg of catalyst and 10 mL of deionized water were weighed and added to a high-temperature and high-pressure resistant transparent reactor, which was then sealed. The reactor was then flushed with carbon dioxide gas through the inlet for 15 min to remove residual air; the exhaust valve was closed, and the carbon dioxide pressure was stabilized at 0.1 MPa. To establish adsorption equilibrium, the reactor was magnetically stirred in the dark for 30 min, then irradiated with a 300 W xenon lamp. Simultaneously, the system temperature was kept constant at 250 °C using a temperature control program, and the reaction was started and continued for 2 h. After the reaction, the gas inside the reactor was quantitatively determined using a Shimadzu GC-2014C gas chromatograph.

[0044] Catalyst activity test results are as follows Figure 4 As shown in a, with V S The introduction of [a specific catalyst] significantly improved the photothermal reduction activity of ZnS catalysts for CO2, with amorphous ZnS-3 exhibiting the best catalytic performance. When V [a specific catalyst] was further increased... S At certain concentrations, the catalytic activity actually decreases. This indicates that an appropriate amount of V... S It can optimize the electronic structure of the catalyst, increase CO2 adsorption and activation sites, and promote the separation and migration of photogenerated carriers, thereby improving catalytic activity; however, excess V S This can lead to defect aggregation, forming new carrier recombination centers, and simultaneously increasing the adsorption strength of reaction intermediates, which is detrimental to electron transport and product desorption, ultimately resulting in a decline in catalytic performance. Among them, amorphous ZnS-3 exhibited the highest catalytic activity, with an ethylene formation rate of 744.7 μmol·g⁻¹. -1 ·h -1 Ethane formation rate: 6.5 μmol·g -1·h -1 Furthermore, ethylene accounts for 94.08% of the product, and the yield and selectivity of the main product ethylene are greatly improved, which is beneficial to the separation of subsequent products.

[0045] To further investigate the effect of reaction conditions on the catalytic activity of the catalyst, the activity of ZnS-3 was tested under light, heating, and photothermal conditions, respectively. The results are as follows: Figure 17 As shown in (a), the product formation rate under photothermal conditions is 744.7 μmol·g. -1 ·h -1 The formation rate was significantly higher than that under light and heating conditions, being 24.6 times that under light and 1.26 times that under heating conditions, respectively. Notably, the photothermal catalytic activity was significantly higher than the simple sum of the photocatalytic and thermal catalytic activities, indicating a significant photothermal synergistic effect in the ZnS-3 system. During the photothermal catalytic reaction, the electrons in ZnS-3... - E is formed when excited by light. - -h + The electron-hole pair can participate in the catalytic reduction of CO2, promoting the catalytic reaction. Thermal energy provides the activation energy required for the CO2 reaction, lowering the reaction energy barrier and significantly increasing the rate of the catalytic reaction. Furthermore, the photothermal synergy also helps promote the formation of key C2 intermediates and the CC coupling process, thereby improving ethylene yield and selectivity.

[0046] Since the major product C2H4 exists in gaseous form, the effect of the initial CO2 gas pressure on the reaction rate and the selectivity of the major product was investigated. The results are as follows: Figure 17 As shown in (b), the catalytic activity gradually increases with increasing initial CO2 pressure, reaching a maximum at 0.1 MPa, where the ethylene selectivity reaches 94.08%. At lower pressures, insufficient CO2 coverage on the catalyst surface limits CO2 adsorption activation and subsequent multi-electron reduction processes. With increasing pressure, more CO2 molecules participate in the surface reaction, significantly increasing the ethylene formation rate. However, when the pressure increases further, excessively high CO2 partial pressures enhance competitive adsorption on the catalyst surface, reducing H2O transport efficiency and increasing product desorption resistance, ultimately leading to a decrease in catalytic activity. Therefore, 0.1 MPa is the optimal initial CO2 pressure for this system. Furthermore, the reaction temperature has a significant impact on CO2 catalytic reduction. We conducted temperature gradient tests on ZnS-3, and the results are shown below. Figure 17As shown in (c), the reaction activity gradually increases with increasing reaction temperature, reaching its optimal value at 250 °C, where the selectivity for ethylene is highest. With increasing reaction temperature, the reaction system receives more energy, providing the activation energy required for the CO2 reaction, lowering the reaction energy barrier, and thus continuously increasing the rate of the catalytic reaction. This indicates that 250 °C is the optimal temperature for this catalyst to catalyze the production of ethylene from CO2, and that this temperature is the optimal temperature condition for ethylene production.

[0047] To investigate the effect of light intensity on the catalytic reduction of CO2, we conducted experiments on amorphous ZnS-3 at different wavelength bandpass plates at the optimal temperature of 250 ℃. The results are as follows: Figure 17 As shown in (d), the catalytic activity is 651.38 μmol·g under 420 nm illumination. -1 ·h -1 The values ​​were higher than 572.44, 596.48, 558.02, and 549.32 μmol·g at illumination intensities of 400, 450, 500, and 550 nm, respectively. -1 ·h -1 The catalytic activity was significantly improved, indicating that amorphous ZnS-3 exhibits the best catalytic performance under 420 nm excitation during the catalytic reaction.

[0048] Cyclic experiments were conducted on amorphous ZnS-3, and the results are as follows: Figure 17 As shown in (e), after five cycles of photothermal catalytic CO2 reduction, the catalytic activity of amorphous ZnS-3 did not decrease significantly, indicating that amorphous ZnS-3 has good stability and can maintain its catalytic activity for a long time in the photothermal catalytic CO2 reduction system.

[0049] The surface optical properties of catalysts can be studied using ultraviolet-visible diffuse reflectance spectroscopy (UV-vis DRS). To quantitatively characterize bandgap changes, the Kubelka-Munk formula can be used to convert DRS data into Tauc curves. Figure 18 The figures show the band gaps of crystalline ZnS₁ and amorphous ZnS₃. The band gap width determines the response range of a semiconductor to different wavelengths of light, and is a crucial parameter affecting light absorption and photocatalytic performance. The results show that the band gap width of crystalline ZnS₁ is 3.72 eV. By adjusting the band gap at different wavelengths... S After adjusting the concentration, the ZnS-3 catalyst not only underwent a change in crystal structure but also showed a slight adjustment in band gap width, which became 3.34 eV. A narrower band gap allows for better absorption of visible light, enhancing the photocatalytic performance of the catalyst. This indicates that the amorphization treatment affects the optical properties of the catalyst. The conduction band (CB) of the catalyst was obtained through MS curve analysis. Figure 19The MS curves of crystalline ZnS-1 and amorphous ZnS-3 are shown, respectively, with the conduction band (CB) of the catalysts being 1.05 eV and 1.42 eV, respectively.

[0050] XPS analysis further verified the chemical composition and electron transfer direction of the amorphous ZnS-3 catalyst under different conditions. Figure 4 As shown in (b), Zn 2p The high-resolution XPS spectrum of amorphous ZnS-3 shows peaks located at Zn 2p 3 / 2 (1019.65 eV) and Zn 2p 1 / 2 (1042.57 eV) After the reaction, the binding energy of Zn increased by about 0.27 eV, indicating that the electron density around Zn decreased and the Zn site exhibited stronger Lewis acidity, which is conducive to the adsorption and activation of CO2 molecules. Figure 4 (c) Showing the binding energy of S S 2p 3 / 2 (161.70 eV) and S 2p 1 / 2 (162.93 eV) Towards lower binding energy S 2p 3 / 2 (161.56 eV) and S 2p 1 / 2 (162.72 eV) transfer. In summary, the binding energy of Zn increases as it loses electrons, while the binding energy of S decreases, representing the gain of electrons. Electrons transfer from Zn to S. Furthermore, Figure 20 The Zn and S characteristic peak positions of amorphous ZnS-3 before and after the reaction remained basically consistent, indicating that the catalyst has good chemical stability. Furthermore, the reaction pathway given based on in-situ FT-IR (photothermal + thermal) results was compared with in-situ FT-IR of different catalysts using photothermal, single-photothermal, and single-thermal methods, revealing the different effects of amorphous ZnS-3 on CC coupling and key intermediates in CO2 reduction.

[0051] To investigate the key role of photothermal synergy in the efficient photoreduction of CO2 to C2H4, in-situ Fourier transform infrared spectroscopy (FTIR) was performed on amorphous ZnS-3 and amorphous ZnS-5 to explore the evolution of intermediates during CO2 adsorption activation and photothermal catalytic reaction. The results are as follows: Figure 4 (d) and Figure 21 As shown. Compared with amorphous ZnS-5, amorphous ZnS-3 shows a significantly enhanced overall infrared absorption signal, indicating that an appropriate amount of V... SThe induced interfacial electron redistribution enhanced the catalyst's adsorption and activation capacity for CO2. Further in-situ FTIR dynamic measurements of ZnS-3 under photothermal conditions (0-120 min) were conducted to monitor the formation and evolution of surface intermediates during the catalytic process. Figure 4 As shown in (d), at 924, 1328, 1397 and 1471 cm -1 Carbonate species formed by CO2 adsorption were observed at various locations, including 1328 cm⁻¹. -1 Corresponding bidentate carbonate (β-CO3) 2- ), 1397 and 1471 cm -1 Corresponding monodentate carbonate (m-CO3) 2- This indicates that CO2 molecules can be effectively adsorbed and activated on the ZnS-3 surface. With increasing photothermal reaction time, the values ​​at 1545 and 1611 cm⁻¹... -1 The characteristic peak at 2091 cm⁻¹ gradually intensifies and can be attributed to the vibrational peaks of the *COOH intermediate, indicating that CO₂ first undergoes proton-coupled electron transfer to form *COOH, which is a key initial intermediate in the CO₂ reduction process. Subsequently, at 2091 cm⁻¹... -1 A distinct CO adsorption peak was detected at [value missing]. *CO is widely considered an important precursor for C2 product formation via CC coupling; its continuous accumulation indicates that ZnS-3 can promote the formation of the *CO intermediate, providing favorable conditions for subsequent ethylene formation. 2238 cm⁻¹ -1 The characteristic peak at 3566 cm⁻¹ belongs to the asymmetric stretching vibration of gaseous CO₂, indicating that CO₂ was continuously introduced during the in-situ test. Meanwhile, at 3566 cm⁻¹... -1 HCO3 was detected at the site - Species, at 3612 cm -1 The stretching vibration of OH groups adsorbed with H2O was observed at 3619 cm⁻¹. -1 The presence of OH species on the corresponding surface indicates that H2O not only participates in proton supply but also in the proton transfer process on the catalyst surface. Combined with in-situ FTIR results, it can be seen that under the synergistic effect of photothermal action, CO2 first adsorbs onto the ZnS-3 surface to form carbonate species, subsequently undergoing key intermediates such as *COOH and *CO, and further undergoing CC coupling to form C2 products. A suitable amount of V S The induced electron redistribution enhances the adsorption and activation capacity of CO2, accelerates the generation and transformation of key intermediates, and thus promotes the highly selective generation of ethylene.

[0052] Based on the above analysis, we propose V S The possible catalytic mechanism of induced amorphous ZnS-3 in the photothermal catalytic selective reduction of CO2 is as follows: First, V S Doping into the ZnS-1 crystal lattice in the form of defects, due to VS The continuous accumulation of defects leads to the transformation of crystalline ZnS-1 into amorphous ZnS-3. The Zn-S bond length shortens, increasing CO2 adsorption. However, the excessive addition of sulfur vacancies results in excessive lattice distortion in amorphous ZnS-5, increasing the adsorption of reaction intermediates and hindering subsequent reactions. During the reaction, electrons from Zn begin to transfer to S, reducing the electron cloud density around Zn and enhancing its Lewis acidity, thus increasing its binding capacity for O and laying the groundwork for strong CO2 adsorption later. At the start of the photothermal catalytic reaction, amorphous ZnS-3 utilizes light energy to provide initial electrons and holes, lowering the reaction energy barrier and enabling the catalytic reaction to begin with high selectivity. Thermal energy promotes the adsorption and desorption of reactants, accelerates vacancy turnover and reaction site circulation, maintaining a high reactant coverage on the catalyst surface and ensuring the active sites remain in a cyclical state. The synergistic effect of light and heat energy, complementing each other, achieves low-temperature, high-rate, and highly selective CO2 reduction. The specific reaction formula is as follows: H2O → H + + OH - ; *CO2+ H + + e - → *COOH; *COOH + H + + e - → *CO + H2O; *CO + *CO → *OCCO; *OCCO + H + + e - → *OCCHO; *OCCHO + H + + e - → *CHOCHO; *CHOCHO+H + + e - → *CH2OCHO; *CH2OCHO + H + + e - → *CH2OCH2O; *CH2OCH2O + H + + e - → *CH2OCH2OH; *CH2OCH2OH + H + + e - → *CH2OHCH2OH; *CH2OHCH2OH + H + + e -→ *CH2CH2OH + H2O; *CH2CH2OH + H + + e - → *CH2CH2+ H2O.

[0053] By integrating the above experimental data, we obtained the following results: Figure 5 The mechanism diagram shown.

[0054] This invention achieves precise control of V S Concentration, successfully constructed a V S The dominant amorphous ZnS photothermal catalyst, namely ZnS-3, was systematically elucidated through various structural characterizations, in-situ infrared spectroscopy, and DFT calculations. S The effects of induced amorphization on catalyst electronic structure, CO2 adsorption activation, carrier migration, and the evolution of key intermediates were investigated. Results showed that an appropriate amount of V... S This process not only promotes the transformation of ZnS from crystalline to amorphous states but also optimizes the local coordination environment and electronic structure, enhances CO2 adsorption capacity, promotes the separation and migration of photogenerated carriers, and accelerates the formation of key intermediates such as *COOH and *CO, as well as subsequent CC coupling processes. Under optimal reaction conditions, amorphous ZnS-3 can achieve highly efficient photothermal catalytic CO2 reduction without the addition of organic solvents or co-catalysts, achieving an ethylene production rate of 744.7 μmol·g⁻¹. -1 ·h -1 The ethylene selectivity reached 94.08%, and its catalytic performance was significantly better than that of pure photocatalysis and pure thermocatalysis systems, confirming a significant synergistic promoting effect between light and heat energy. This invention discloses V S The mechanism by which Zn active sites synergistically regulate electronic structure and interfacial reaction kinetics provides a new design strategy for constructing low-cost, high-efficiency amorphous sulfide photothermal catalysts, and also offers new research ideas for the high-selectivity conversion of CO2 into high-value-added C2 chemicals.

[0055] Obviously, those skilled in the art can make various modifications and variations to the embodiments of the present invention without departing from the spirit and scope of the invention. Therefore, if these modifications and variations fall within the scope of the claims of the present invention and their equivalents, the present invention also intends to include these modifications and variations.

Claims

1. An application of amorphous ZnS-3, characterized in that, The amorphous ZnS-3 serves as a catalyst for the efficient photothermal synergistic reduction of CO2 to ethylene. In the amorphous ZnS-3, the molar ratio of zinc to sulfur is 1:

3.

2. The application of amorphous ZnS-3 according to claim 1, characterized in that, The method for reducing CO2 to produce ethylene includes the following steps: Weigh the amorphous ZnS-3 and deionized water at a solid-liquid mass ratio of 1:200, add them to the reaction vessel and seal it. Rinse the reaction vessel with carbon dioxide gas through the air inlet for 14-16 minutes to remove residual air. Close the exhaust valve and stabilize the carbon dioxide pressure at 0.09-0.11 MPa. Stir magnetically for 25-35 minutes in the dark, then turn on the 250-350 W xenon lamp and set it to 245-255 ℃. Start timing and let the reaction continue for 1-3 hours.

3. The method for preparing amorphous ZnS-3 according to claim 1, comprising the following steps: Weigh zinc nitrate hexahydrate solid and thiourea solid into a reaction vessel; Add ethylene glycol, stir, and label this solution A. The solution A is transferred to an autoclave for reaction; The white powder was collected by centrifugation, and then washed 2-4 times alternately with ultrapure water and ethanol. The precipitate was dried in a vacuum environment to obtain amorphous ZnS-3.

4. The preparation method according to claim 3, characterized in that, The content of the ethylene glycol is 60-80 mL, and the concentration is ≥99.5%.

5. The preparation method according to claim 3, characterized in that, Set the stirring speed to 400-600 rpm and the stirring time to 40-50 min.

6. The preparation method according to claim 3, characterized in that, The reaction temperature was set at 160-200 ℃, and the reaction time was set at 8-12 h.

7. The preparation method according to claim 3, characterized in that, Set the drying temperature to 50-70 ℃.